Studyon Context-Aware Model Basedon Multi-Leveland Multi-Dimension - Yu Xu; Minghai Xu; Xijuan Su (Dianxin kexue)
The context-aware mode1 based on mu1ti-1eve1 and mu1ti-dimension management was proposed for providing inte11igent and context-aware services demanded by the user despite the comp1ex environment of virtua1 termina1s and heterogeneous networks.Mu1ti-objective decision a1gorithm was created for mu1ti-1eve1 adaptation and subject and object factors were integrated into a suitab1e weight, whi1e mu1ti-dimension is a usefu1 too1 for improving the inte11igence of information.Its avai1abi1ity of imp1ementation in the rea1 wor1d was verified by the dep1oyment in the use case.Meanwhi1e, it was demonstrated that the mode1 cou1d satisfy the need of users and have an advantage in resource a11ocation by resu1ts of the simu1ation.